The Books of King Sigismund at Uppsala University Library - Sjökvist, Peter (Scando-slavica, 2022)
When Uppsala University Library was formally founded in 1620 and 1621, the book depot of the Crown, previously located on Gråmunkeholmen (today's Riddarholmen) in Stockholm, was donated there. This collection inter alia contained the confiscated library of a Swedish nobleman and remnants from medieval Swedish monastery libraries. As Otto Walde conclusively proved in 1915, it also contained the Swedish parts of the library of the Swedish King Sigismund (Sigismund III in Poland), who was dethroned in Sweden in 1599. Sigismund's books were soon scattered and spread among the rest of the book collections of Uppsala University Library, which were arranged according to subject, without any indication of provenance. The aim of the present article is to report what we currently know about Sigismund's collection. Step by step, not least by the research of Otto Walde, but also by the ongoing work at the library, we are now able to know more titles and much more about the contents and destinies of this Royal book collection than what was previously known.